Numerical Algebra, Matrix Theory, Differential-Algebraic Equations and Control Theory 2015
DOI: 10.1007/978-3-319-15260-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial Eigenvalue Problems: Theory, Computation, and Structure

Abstract: Matrix polynomial eigenproblems arise in many application areas, both directly and as approximations for more general nonlinear eigenproblems. One of the most common strategies for solving a polynomial eigenproblem is via a linearization, which replaces the matrix polynomial by a matrix pencil with the same spectrum, and then computes with the pencil. Many matrix polynomials arising from applications have additional algebraic structure, leading to symmetries in the spectrum that are important for any computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…For several other structured classes of matrix polynomials of odd grade there are indeed structure preserving companion linearizations [16,38,39] (see also [15,Sect. 7] and [41], and the references therein), but there are no stratification results available in the literature for these structures. Since in this paper the stratification results for skew-symmetric pencils and polynomials previously developed in [19,22] have played a key role, we see again that the techniques of this paper cannot be directly used to get similar results for other structured matrix polynomials.…”
Section: Discussionmentioning
confidence: 99%
“…For several other structured classes of matrix polynomials of odd grade there are indeed structure preserving companion linearizations [16,38,39] (see also [15,Sect. 7] and [41], and the references therein), but there are no stratification results available in the literature for these structures. Since in this paper the stratification results for skew-symmetric pencils and polynomials previously developed in [19,22] have played a key role, we see again that the techniques of this paper cannot be directly used to get similar results for other structured matrix polynomials.…”
Section: Discussionmentioning
confidence: 99%
“…. , k, we have that the orthogonal complement, computed with the Gram-Schmidt process, is ψ ⊥ (θ) = ψ(θ) − Ψ k (θ)h. Using the Observation 4 we obtain directly (23). We express ψ(θ) as (16) and, the columns of Ψ k as…”
Section: Orthogonalizationmentioning
confidence: 99%
“…For instance, it was shown that constructing pencils in these spaces corresponding to a given ansatz vector is very simple and almost all the resulting pencils are linearizations of P(λ ) from which the eigenvalues and corresponding eigenvectors can be easily recovered. In further work [18,20,12], it was shown that if P(λ ) has some special structure like, Hermitian, symmetric, ⋆-alternating and ⋆-palindromic, (see [22] for definitions), then there exist subspaces of L 1 (P) and L 2 (P) with the property that almost every pencil of the subspace is a structure preserving linearization of P(λ ) from which both finite and infinite eigenvalues of P(λ ) and corresponding eigenvectors can be easily recovered.…”
Section: Introductionmentioning
confidence: 99%